If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5e + -3) = e + 4 Reorder the terms: 3(-3 + 5e) = e + 4 (-3 * 3 + 5e * 3) = e + 4 (-9 + 15e) = e + 4 Reorder the terms: -9 + 15e = 4 + e Solving -9 + 15e = 4 + e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-1e' to each side of the equation. -9 + 15e + -1e = 4 + e + -1e Combine like terms: 15e + -1e = 14e -9 + 14e = 4 + e + -1e Combine like terms: e + -1e = 0 -9 + 14e = 4 + 0 -9 + 14e = 4 Add '9' to each side of the equation. -9 + 9 + 14e = 4 + 9 Combine like terms: -9 + 9 = 0 0 + 14e = 4 + 9 14e = 4 + 9 Combine like terms: 4 + 9 = 13 14e = 13 Divide each side by '14'. e = 0.9285714286 Simplifying e = 0.9285714286
| 6a+a=84 | | 30(6)+5y=90 | | X-43=-4x+27 | | 8x+10y=12-8x | | .45x=9 | | 140+2x-y=180 | | 3(5x-5)=x+10 | | 0=4.9t^2-14.7t | | 20x-x^2=100 | | 3+5h=7+2h | | 8(4r-9)=r+27 | | x+(x+4)+(x+8)=21 | | -7-(n-1)=-6(1-2n) | | y=x^2+7x+9 | | 4x-11=x-9 | | 3a+3=54 | | 8(-1+5x)=112 | | 30=9x+y | | x+10-7=4(x+6)-2(3x+3) | | 103-x=2x+6x-7 | | 8w-13w=25 | | 7b^2+-14b+1=0 | | 4x+11=5x-5 | | 4x+8=2x+31+51 | | 12+40=62 | | 3k-1=7x+2 | | 6+2(x+7)=10-3(x-3) | | 40x^2-x+4000=0 | | 5x+11=5x-5 | | 16+8y=48 | | -1+2-(-3)=10 | | -4j=39 |